Принцип игровой пародийности в художественном. тексте Григория Остера „Вредные советы” - Dorota Horczak (Studia Rossica Posnaniensia)
This article is devoted to analyzing parodic play in Harmful Advice by Grigorij Oster. The game’s strategy in this text combines elements of the classical and post-modern interpretation of literary parody. By using the style of children’s literature, Oster exposes and parodies what is absurd in human thinking and behavior.